(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses various skills for developing independent work when teaching English. The features of the organization of training at a technical university and the specifics of the teaching methods used and the degree of independence of students are also analyzed.